England Policy in Gifted Education: Current Problems and Promising Directions. Issue 2 (April 2018) - Koshy, Valsa; Smith, Carole Portman; Casey, Ronald
This article presents and analyzes policies in identification and provisions in England with respect to gifted education. England has developed a national policy to provide services to identified students. Surveys and interviews with teachers illustrate how implementation of both identification and provision policy elements were handled. Although policy evaluation was conducted by an external ministry agency, it appears to have had little impact on practice. The article suggests that policy implementation, if left to local schools in the absence of monitoring controls, results in lack of services to gifted children in local school environments.